Change in the prevalence of prehypertension and hypertension among young Indians aged 15–24 years between 2015–16 and 2019–21: Insights from nationally representative surveys - Zahid Ali Khan; Uruj Qureshi; Tazeen Khan; Sonu Goel (PLoS ONE, 2025)
Globally, the prevalence of prehypertension and hypertension among adults in low- and middle-income countries is on the rise. However, the data on young people remains scarce. In this context, we analyzed data from two national-level cross-sectional surveys—NFHS–4, which included 272,966 individuals, and NFHS–5, which included 250,213 individuals—to assess changes in the prevalence of prehypertension and hypertension among young Indians aged 15–24 years. Between 2015–2016 and 2019–2021, the prevalence of prehypertension increased significantly (p <  0.001), rising from 38.9% to 44.5% among men and from 21.1% to 26.9% among women. While hypertension prevalence among men increased from 5.2% to 6.2%, it remained stable at approximately 4.0% among women over the same period. Most states, with a few exceptions, exhibited an increase in prehypertension prevalence across both genders, and more than two-thirds of states also showed an increase in hypertension prevalence among men. High BMI was found to be strongly associated with both prehypertension and hypertension. The rising prevalence of prehypertension and hypertension among young Indians aged 15–24 years is concerning and underscores the urgent need to develop targeted preventive strategies for this age group.